P133 Approaching Economic Evaluation in Social Care Guidance. (15th August 2013) - Smith, T; Shaw, E; Baillie, N
Abstract : Background: We have a statutory responsibility to produce social care guidance. For economic evaluation challenges include: 1. Methodology for a multi-stakeholder perspective (costs and outcomes), and determining measures of effects using standardised outcomes. 2. Decision making in the absence of accepted willingness to pay thresholds, and alignment with principles used for health guidelines. Objectives: To define an economic reference case for social care guidance. Methods: A workshop on methods identified potential approaches. Health economists who work on clinical and public health guidelines were consulted to ensure consistency. Methodological issues were discussed with academic experts. Results: A reference case for social care economic evaluation was produced within a methods manual before commencing guidance development. It recognises the need for flexibility as methodology develops. Discussion: Social care economic evaluation is constrained by the quality of evidence, and the transferability of studies. Equity considerations in the context of means-tested service provision, and the issue of unpaid care, represent examples of how decision making on cost-effectiveness must take account of factors not usually considered for clinical and public health guidelines. Implications for Guideline Developers/Users: Consistent decision-making principles must be applied across all guidance development programmes, including social care cost-effectiveness. Social care guidance, developers need to recognise and work within the context of emerging methodologies when undertaking social care economic evaluation in, but ensure that such evaluations remain in line with general principles of guidance development and decision making.